Validation of Atmospheric Wind Fields from MIGHTI/ICON: A Comprehensively Comparative Analysis with Meteor Radars, FPI and TIMED/TIDI - Dini Gong; Shengyang Gu; Yusong Qin; Na Li; Yiding Chen; Wei Yuan; Yafei Wei (Remote Sensing)
The Michelson interferometer for global high-resolution thermospheric imaging (MIGHTI) aboard the NASA ionospheric connection (ICON) satellite offers extensive atmospheric wind field data for mid-latitude regions and has recently released its version 5 (v05) data. We conducted a comprehensive comparison and validation of MIGHTI v05 level 2.2 data for the period from December 2019 to October 2022, covering all MIGHTI data in orbit. In a comparison of raw wind speeds, MIGHTI demonstrates good agreement with the ground-based Fabry–Pérot interferometer (FPI), meteor radars, and the space-borne instrument TIMED Doppler interferometer (TIDI). However, some differences still exist. Comparisons with meteor radars revealed differences attributable to observational altitude, day–night variations, and latitude distribution. Below 100 km, MIGHTI and meteor radar exhibit excellent consistency (r = 0.819 for zonal and r = 0.782 for meridional winds). Day–night differences are minimal, with closer amplitude values observed at night. MIGHTI shows stronger correlations with low-latitude meteor radar, with coefficients of 0.859 (zonal) and 0.891 (meridional) at Ledong. The meridional wind correlation is better in low-latitude regions, in contrast to mid-latitudes. Similar observations were made in a comparison with FPI, emphasizing the need for caution when considering the meridional wind component of MIGHTI at observational boundaries (~40 °N). In addition to comparing raw wind speed data, we analyzed the amplitude of fluctuations extracted by MIGHTI and TIDI by employing the least squares method to extract planetary waves. The results indicate that both TIDI and MIGHTI observe the same fluctuation events, but TIDI extracts larger fluctuation amplitudes than MIGHTI. Finally, we present, for the first time, the spatial structure of a five-day wave that occurred in March 2020.